Optimizing rating scales of the big five socialization scale in athletes by Rasch model - Bartholomeu, Daniel (2016)
Personality is one of the main psychological aspects that influence athletes performance in competition and one of the most studied subjects in sport psychology. We aimed to optimize item scales in a socialization test based on the big-five model, assessed by means of adjectives and administered to a sample of 225 athletes of both sexes, with 56.9% male. Age ranged from 14-45 years with a mean of 20 (SD = 5,21). Participants attended to basketball (11%), Football (21.8%), Handball (17.3%), Jiu-jitsu (10.2%), tennis (5.60) and Volleyball (16 %) sport modalities. The results indicated that the four point scale were the best item scale structure regarding validity evidences. Hence, this structure could be adopted in this scale aiming better socialization assessment in athletes.